A compact multimode broadband dual‐polarized base station antenna for LTE and 5G applications. Issue 5 (18th February 2021) - Huo, Yu; Zhang, Kunming; Guo, Chaozong; Zhai, Huiqing; Zeng, Yi
Abstract: A compact multimode broadband ±45° dual‐polarized base station antenna for LTE and 5G applications is proposed. By introducing folded circular ring dipoles loaded with short wires into the stepped square ring dipoles to create a new resonance mode at high frequency to achieve the purpose of extending the bandwidth. Simulation and experiment show that the antenna can achieve a bandwidth of 55.9% (2.28‐4.05 GHz) within the operating frequency (|S11| < −15 dB and |S21| < −25 dB), and the proposed antenna has a measured gain about 8.3 ± 0.9 dBi and a cross polarization ratio greater than 25 dB.